Fe-carbon hybrid composite interlayer for improved electrochemical performance of Li-S battery. (1st January 2022) - Kumar, S. Krishna; Gaikwad, Mayur M.; Rani, Poonam; Pathak, Anil D.; Sharma, Chandra S.
Highlights: Iron (Fe) is used as catalyst to derive partially graphitized RF carbon xerogel. Fe-catalysts cause local graphitization within amorphous carbon matrix. Fe embedded partially graphitized hard carbon is used as interlayer [Fe-G-HC-IL]. Fe-G-HC-IL improves the electrochemical performance of modified Li-S battery. Electro-catalytic activity of Fe converts Li-polysulfides species to redox products. Abstract: The major bottlenecks in achieving the full potential of Lithium-sulfur (Li-S) batteries are the insulating nature of sulfur and Li-polysulfide (Li-PS) shuttling which lead to their poor rate performance and cyclic stability. In this work, we solve these critical issues using a unique Fe-carbon hybrid composite interlayer prepared by the catalytic graphitization of resorcinol formaldehyde (RF) xerogel. The physicochemical characterizations of the interlayer material reveal that it consists of iron-nanoparticles encapsulated by graphitic carbon within the amorphous RF xerogel derived hard carbon matrix (Fe-G-HC-IL). The Li-S battery, with Fe-G-HC-IL as a functional separator and activated candle soot-sulfur composite cathode, demonstrates a significantly improved electrochemical performance than without the interlayer. The Li-S battery with Fe-G-HC-IL shows the capacity of 1057 mAh g −1 at 1 C-rate with a decay rate of 0.055% per cycle and excellent rate capability. Further, density functional theory (DFT) calculation indicates that the Fe embedded carbon structure present in interlayer composite contributes significantly to the improvement in the conductivity and minimization of Li-PS shuttling. Additionally, this Fe-carbon hybrid structure electro catalyzes the conversion of Li-PS to desired end products of the redox reactions which further enhance the electrochemical performance of Li–S batteries. Graphical abstract: Image, graphical abstract